Solid electrolyte and preparation method thereof
By using a solid electrolyte with chemical formula as LI6-XPS5-XCl1+X, it controls its particle size and water content, solving the problem of low existing solid electrolyte ion conductivity and poor air stability, which significantly improves the performance of the battery.
Patent Information
- Application Number
- CN202411780463.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-28
AI Technical Summary
The ionic conductivity of existing solid electrolytes is not high and the air stability is poor, which affects the performance of solid electrolyte batteries.
The solid electrolyte with chemical formula is li6-XPS5-XCl1+X, 0≤x ≤ 0.6, and controls its D50 to 1-15 μm and moisture content below 300ppm, reducing moisture content, increasing air stability and ionic conductivity.
Effectively improve the air stability of solid electrolytes and ionic conductivity, reduce the occurrence of side effects, and improve the overall performance of the battery.
Smart Images

Figure CN119381540A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a solid electrolyte and a preparation method thereof. Background Art
[0002] Solid-state electrolyte batteries have higher energy density and can store more energy. In addition, solid-state electrolyte batteries are safer because solid electrolytes are non-flammable, reducing the risk of fire. Therefore, solid-state electrolytes have significant advantages in battery technology.
[0003] However, current solid-state electrolytes still have defects, such as low ion conductivity and poor air stability, which affect the performance of solid-state electrolyte batteries. Summary of the invention
[0004] The object of the present invention is to provide a solid electrolyte and a preparation method thereof, which improves the ionic conductivity of the solid electrolyte and increases the air stability of the solid electrolyte, thereby increasing the overall performance of the battery.
[0005] To achieve the above object, in a first aspect, the present invention provides a solid electrolyte, the chemical formula of which is: Li 6-x PS 5-x Cl 1+x , 0≤X≤0.6, D50 of the solid electrolyte is 1-15μm, and the moisture content in the solid electrolyte is below 300ppm. The beneficial effect of the solid electrolyte provided by the present invention is that: by using the chemical formula Li 6-x PS 5-x Cl 1+x The solid electrolyte with a D50 of 0≤X≤0.6 can effectively reduce the moisture in the solid electrolyte by utilizing its characteristics of D50 of 1-15μm and moisture content below 300ppm, thereby making the solid electrolyte have strong air stability and high ion conductivity. The occurrence of side reactions can be effectively reduced when preparing battery cells, thereby improving battery performance.
[0006] In some embodiments, the ionic conductivity of the solid electrolyte is greater than 2.5 mS / cm. The beneficial effect is that: by utilizing the property of the ionic conductivity of the solid electrolyte provided by the present invention being greater than 2.5 mS / cm, the solid electrolyte is used in battery preparation, which can effectively improve various performances of the battery.
[0007] In some embodiments, the impurities of the solid electrolyte include at least one of Na, Ca, Fe, and Cu, and the impurities of the solid electrolyte are less than 1%. The beneficial effect is that since the impurities of the solid electrolyte provided by the present invention are less than 1%, the migration environment of ions is optimized, the ion conductivity is improved, and the electrochemical stability of the solid electrolyte is also improved, thereby extending the service life of the battery.
[0008] In some embodiments, the purity of the solid electrolyte is not less than 99.9%. The beneficial effect is that the purity of the solid electrolyte is not less than 99.9%, so its impurity content is low, thereby improving the ionic conductivity and electrochemical stability of the solid electrolyte.
[0009] In some embodiments, when the chemical formula of the solid electrolyte further includes Br, the chemical formula of the solid electrolyte is: Li 6-x PS 5-x ClBr x , 0.25≤X≤0.75. Its beneficial effect is that by adding Br into the matrix electrolyte, its electrochemical performance and structural stability are improved.
[0010] In some embodiments, when the chemical formula of the solid electrolyte also includes O, the chemical formula of the solid electrolyte is: Li6PS 5-x C1O x , 0.25≤X≤1. Its beneficial effect is that by adding O element into the matrix electrolyte, the crystal phase structure of the solid electrolyte is stabilized and the air stability is improved.
[0011] In another aspect, an embodiment of the present invention provides a method for preparing a solid electrolyte, which can be used to prepare the solid electrolyte. The preparation method includes: The required raw materials are mixed to obtain a mixed material, and the mixed material is sintered and then crushed to obtain the solid electrolyte.
[0012] In some embodiments, an inert gas is introduced into the mixing process, the sintering process, and the crushing process to make the moisture content in the solid electrolyte below 300 ppm; The D50 of the solid electrolyte is 1-15 μm. The beneficial effect is that the moisture content in the solid electrolyte can be effectively controlled by introducing inert gas during the mixing process, sintering process and crushing process, so that the moisture content in the solid electrolyte is below 300 ppm. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a schematic diagram of the structure of the solid electrolyte provided in the embodiment of the present invention when the particle size is less than 1 μm; Figure 2 This is a schematic diagram of the structure of the solid electrolyte provided in the embodiment of the present invention when the particle size is greater than 1 μm; Figure 3 The present invention provides a flow chart of a method for preparing a solid electrolyte according to an embodiment of the present invention. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the usual meanings understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Unless otherwise specified, the "connection" described in this article can be a direct connection or an indirect connection, that is, connected through an intermediate.
[0015] Although solid-state electrolytes have significant advantages in battery technology, current solid-state electrolytes still have defects, such as low ion conductivity and poor air stability, which affect the performance of solid-state electrolyte batteries.
[0016] In view of the problems existing in the prior art, an embodiment of the present invention provides a solid electrolyte, referring to Figure 1 and Figure 2 As shown, the chemical formula of the solid electrolyte is: Li 6-x PS 5-x Cl 1+x , 0≤X≤0.6, the shape of the solid electrolyte includes a spherical shape, the D50 of the solid electrolyte is 1-15μm, and the moisture content in the solid electrolyte is below 300ppm.
[0017] In this embodiment, by using the chemical formula Li 6-x PS 5-x Cl 1+x , 0≤X≤0.6, using its D50 of 1-15μm and moisture content below 300ppm, can effectively reduce the moisture in the sulfide solid electrolyte, so that the sulfide solid electrolyte has strong air stability and high ion conductivity, which can effectively reduce the occurrence of side reactions when preparing battery cells, thereby improving battery performance.
[0018] It should be noted that the solid electrolyte exists in the form of powder, and the moisture content of the solid electrolyte refers to the moisture content of the powder in the solid electrolyte, which can be measured using a moisture meter according to GB / T 6283-2008. After using a moisture meter to test the existing solid electrolytes sold on the market, it was found that the moisture content of the powder of the existing solid electrolytes currently sold on the market is much greater than 500ppm. After using a moisture meter to test the solid electrolyte in this embodiment, it was found that its moisture content was only below 300ppm, which is much less than the moisture content in the existing solid electrolyte. Therefore, the insulation and heat dissipation of the diaphragm prepared using the solid electrolyte provided in this embodiment are greatly improved, which greatly increases the conductivity of the battery prepared subsequently, and also improves the safety of the battery.
[0019] In some specific embodiments, the chemical formula of the solid electrolyte may include but is not limited to Li6PS5Cl1, Li 5.9 PS 4.9 Cl 1.1 , Li 5.8 PS 4.8 Cl 1.2 , Li 5.7 PS 4.7 Cl 1.3 , Li 5.6 PS 4.6 Cl 1.4 , Li 5.5 PS 4.5 Cl 1.5 , Li 5.4 PS 4.4 Cl 1.6 .
[0020] In some specific embodiments, the particle size distribution D50 of the solid electrolyte may be any value of 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, or a value between any two values.
[0021] In some embodiments, the solid electrolyte also includes a sheet shape.
[0022] It is understandable that the solid electrolyte has both a sheet-like shape and a spherical shape. Therefore, the shape of the solid electrolyte can be selected according to actual application requirements.
[0023] In some embodiments, the solid electrolyte has an ionic conductivity greater than 2.5 mS / cm.
[0024] In this embodiment, the solid electrolyte provided by the present invention is used as a raw material for the diaphragm coating slurry to prepare a diaphragm, and a battery prepared using the diaphragm greatly improves the internal resistance and rate performance of the battery.
[0025] In some embodiments, the impurities of the solid electrolyte include at least one of Na, Ca, Fe, and Cu, and the impurities of the solid electrolyte are less than 1%.
[0026] Furthermore, the purity of the solid electrolyte is not less than 99.9%.
[0027] In this embodiment, since the impurities in the solid electrolyte are less than 1%, the migration environment of ions is optimized, the ion conductivity is improved, and the electrochemical stability of the solid electrolyte is also improved, thereby extending the service life of the battery.
[0028] In some embodiments, when the chemical formula of the solid electrolyte further includes Br, the chemical formula of the solid electrolyte is: Li 6-x PS 5-x ClBr x , 0.25≤X≤0.75.
[0029] In this embodiment, when preparing the solid electrolyte in this embodiment, some specific elements or compounds may be doped. For example, in this embodiment, bromine (Br) is doped when preparing the solid electrolyte, so the chemical formula of the prepared solid electrolyte is: Li 6-x PS 5-x ClBr x , 0.25≤X≤0.75. By adding Br into the matrix electrolyte, the electrochemical performance and structural stability of the solid electrolyte are improved.
[0030] In some specific embodiments, the chemical formula of the solid electrolyte may include but is not limited to Li 5.47 PS 4.75 ClBr 0.25 , Li 5.65 PS 4.65 ClBr 0.35 , Li 5.55 PS 4.55 ClBr 0.45 , Li 5.45 PS 4.45 ClBr 0.55 , Li 5.35 PS 4.35 ClBr 0.65 , Li 5.25 PS 4.25 ClBr 0.75 .
[0031] In other embodiments, oxygen (O) may be doped into the matrix electrolyte when preparing the solid electrolyte, and the chemical formula of the solid electrolyte finally obtained is: Li6PS 5-x C1O x , 0.25≤X≤1. By adding O element into the matrix electrolyte, the crystal phase structure of the solid electrolyte is stabilized and the transport of ions is promoted.
[0032] Specifically, the chemical formula of the solid electrolyte may include but is not limited to Li6PS 4.75 C1O 0.25 、Li6PS 4.7 C1O 0.3 、Li6PS 4.5 C1O 0.5 、Li6PS 4.3 C1O 0.7 、Li6PS 4.2 C1O 0.8 、Li6PS 4.1 C1O 0.9 、Li6PS4ClO1.
[0033] It should be noted that in order to prove that the solid electrolyte provided by the present invention has better performance than the existing solid electrolyte, the solid electrolyte provided by the present invention is tested. This test is based on two Li 5.5 PS 4.5 Cl 1.5 and Li 5.25 PS 4.25 ClBr 0.75 Among them, two kinds of Li with different particle sizes 5.5 PS 4.5 Cl 1.5 According to the particle size, it can be divided into basic solid electrolyte and small particle size solid electrolyte. 5.25 PS 4.25 ClBr 0.75 It is a doped solid electrolyte. Specifically, the test results are shown in Table 1 below:
[0034] Table 1 It can be seen from Table 1 that the D50 of the tested solid electrolyte in this embodiment is in the range of 1-15 μm, the ion conductivity of the three tested solid electrolytes is greater than 2.5 mS / cm, and the impurity content of the three solid electrolytes is less than 1%.
[0035] In addition, the instruments used in this test are laser particle size tester, AC impedance meter and X-ray powder diffractometer. Among them, the laser particle size tester is used to test the particle size of the solid electrolyte, the AC impedance meter is used to test the electronic conductivity of the solid electrolyte, and the X-ray powder diffractometer is used to test the impurity content of the solid electrolyte.
[0036] Example 1 After lithium sulfide, lithium chloride and phosphorus pentasulfide are uniformly mixed in a certain proportion, the mixed materials are sintered and then crushed to obtain a solid electrolyte, whose chemical formula is: Li 5.9 PS 4.9 Cl 1.1 . And the moisture content in the solid electrolyte is detected by a moisture detector.
[0037] Example 2 The difference from Example 1 is that the ratio of lithium sulfide, lithium chloride and phosphorus pentasulfide is different. The chemical formula of the prepared solid electrolyte is: Li 5.7 PS 4.7 Cl 1.3 . And the moisture content in the solid electrolyte is detected by a moisture detector.
[0038] Example 3 The difference from Example 1 is that the ratio of lithium sulfide, lithium chloride and phosphorus pentasulfide is different. The chemical formula of the prepared solid electrolyte is: Li 5.4 PS 4.4 Cl 1.6 . And the moisture content in the solid electrolyte is detected by a moisture detector.
[0039] Example 4 After lithium sulfide, phosphorus pentasulfide, lithium chloride and lithium bromide are uniformly mixed in a certain proportion, the mixed materials are sintered and then crushed to obtain a solid electrolyte, the chemical formula of which is: Li 5.25 PS 4.25 ClBr 0.75 . And the moisture content in the solid electrolyte is detected by a moisture detector.
[0040] Example 5 After lithium sulfide, phosphorus pentasulfide, lithium chloride and lithium oxide are uniformly mixed in a certain proportion, the mixed materials are sintered and then crushed to obtain a solid electrolyte, the chemical formula of which is: Li6PS 4.75 C1O 0.25 . And the moisture content in the solid electrolyte is detected by a moisture detector.
[0041] Comparative Example 1 Same as Example 1, except that the moisture content of the solid electrolyte is 350 ppm.
[0042] Comparative Example 2 Same as Example 4, except that the moisture content of the solid electrolyte is 320 ppm.
[0043] Comparative Example 3 Same as Example 5, except that the moisture content of the solid electrolyte is 330 ppm.
[0044] Among them, the moisture contents of the solid electrolytes in Examples 1 to 5 and Comparative Examples 1 to 3 after being tested by a moisture detector are respectively As shown in Table 2 below:
[0045] Table 2 It can be seen from Table 2 that the moisture content of the solid electrolytes in Examples 1, 2, 3, 4 and 5 is all below 300 ppm, which is much lower than the moisture content of the existing solid electrolytes on the market.
[0046] The ionic conductivity of Example 1 is 5.67mS / cm, and the ionic conductivity of Comparative Example 1 is 4.87mmS / cm, and the ionic conductivity of Example 1 is higher than that of Comparative Example 1; the ionic conductivity of Example 4 is 14.97mmS / cm, and the ionic conductivity of Comparative Example 2 is 11.74mmS / cm, and the ionic conductivity of Example 4 is higher than that of Comparative Example 2; the ionic conductivity of Example 5 is 6.85mmS / cm, and the ionic conductivity of Comparative Example 3 is 5.72mmS / cm, and the ionic conductivity of Example 5 is higher than that of Comparative Example 3; it can be seen that under substantially the same conditions, the moisture content of the solid electrolyte of the present invention is low, so that the solid electrolyte of the present invention has a higher ionic conductivity.
[0047] In another embodiment of the present invention, a method for preparing a solid electrolyte is provided, and the preparation method can prepare the solid electrolyte in the above embodiment, referring to Figure 3 As shown, the preparation method comprises: S100: Mixing the required raw materials to obtain a mixed material, sintering the mixed material and then crushing it to obtain the solid electrolyte.
[0048] It should be noted that in this step, in order to effectively control the water content of the solid electrolyte, an inert gas is introduced into the raw materials during the mixing, sintering and crushing processes so that the water content in the solid electrolyte is below 300 ppm. The raw materials include lithium sulfide, lithium chloride and phosphorus pentasulfide.
[0049] Specifically, the raw material mixing process is to put the raw materials into a high-speed mixer for mixing, and pass an inert gas into the high-speed mixer. The sintering process is to put the mixed materials into a closed crucible, and then put the closed crucible into a heating furnace for sintering, and pass an inert gas into the heating furnace to obtain a sintered material. The crushing process is to crush the sintered material into a jet mill after crushing, and pass an inert gas into the jet mill to obtain a solid electrolyte with a moisture content of less than 300ppm.
[0050] In this embodiment, the inert gas may be nitrogen.
[0051] The above is only a specific implementation of the embodiment of the present application, but the protection scope of the embodiment of the present application is not limited thereto, and any changes or replacements within the technical scope disclosed in the embodiment of the present application should be included in the protection scope of the embodiment of the present application. Therefore, the protection scope of the embodiment of the present application should be based on the protection scope of the claims.
Claims
1. A solid electrolyte, characterized in that The chemical formula of the solid electrolyte is: Li 6-x PS 5-x Cl 1+x , 0≤X≤0.6, D50 of the solid electrolyte is 1-15μm, and the moisture content in the solid electrolyte is below 300ppm.
2. The solid electrolyte according to claim 1, characterized in that The ionic conductivity of the solid electrolyte is greater than 2.5 mS / cm.
3. The solid electrolyte according to claim 1, characterized in that Impurities of the solid electrolyte include at least one of Na, Ca, Fe, and Cu, and the impurities of the solid electrolyte are less than 1%.
4. The solid electrolyte according to claim 1, characterized in that The purity of the solid electrolyte is not less than 99.9%.
5. The solid electrolyte according to claim 1, characterized in that When the chemical formula of the solid electrolyte also includes Br, the chemical formula of the solid electrolyte is: Li 6-x PS 5-x ClBr x , 0.25≤X≤0.
75.
6. The solid electrolyte according to claim 1, characterized in that When the chemical formula of the solid electrolyte also includes O, the chemical formula of the solid electrolyte is: Li6PS 5-x C1O x , 0.25≤X≤1.
7. A method for preparing a solid electrolyte, characterized in that: The solid electrolyte according to any one of claims 1 to 6 can be prepared, and the preparation method comprises: The required raw materials are mixed to obtain a mixed material, and the mixed material is sintered and then crushed to obtain the solid electrolyte.
8. The method for preparing a solid electrolyte according to claim 7, characterized in that: Inert gas is introduced into the mixing process, the sintering process and the crushing process so that the moisture content in the solid electrolyte is less than 300 ppm; Wherein, the D50 of the solid electrolyte is 1-15 μm.
Citation Information
Patent Citations
Sulfide solid electrolyte and production method thereof
CN113348577A
Sulfide solid electrolyte, preparation method thereof and all-solid-state lithium battery
CN113659196A
Sulfide solid-state electrolyte, preparation method thereof, solid-state electrolyte sheet and solid-state battery
CN113839086A
Liquid phase preparation method of sulfur-based solid electrolyte, solid electrolyte and lithium-sulfur battery
CN115215308A
Sulfide electrolyte, preparation method thereof and all-solid-state battery
CN118841623A
Cited By
Solid-state electrolyte and preparation method therefor
WO2026118238A1